ANALYSIS OF CHINA COMPLIANCE TO CONVENTION ON ELIMINATION OF ALL FORMS OF DISCRIMINATION AGAINST WOMEN (CEDAW): STUDY CASE OF BRIDE TRAFFICKING IN CHINA - Rafadini, RA. Najmi Sasikirana; Ratnawati (Pena Wimaya, 2026)
This study evaluates China’s compliance to Convention on Elimination of All Forms of Discrimination Against Women (CEDAW) in the response of the rise of case study of Bride Trafficking in China. Past studies about Bride Trafficking have had found that this issue is originated from demographic crisis whereas girls is less than boys in China. Quantitative methods is used to perceive about how China’s managing their policy after ratificate CEDAW to battling Bride Trafficking. There is 3 Indicator that can determine China’s compliance for CEDAW in battling Bride Trafficking; Output, Outcome, and Impact that concluded from Sara McLaughlin Mitchell dan Paul R. Hensel theory. From the Output, China’s already have 2 internal policies, and it allign with the Outcomes that China’s actively seeking for international cooperation mostly in ASEAN. But the Impact revealed that China’s is in the Active category but Non-Compliance. China’s still actively spreading information they know about Bride Trafficking, but ironically this issue is still not over yet. This study aims to contribute to International Relations study, especially about Human Trafficking. Moreover, hopefully this study can helps NGOs or China’s Goverment to construct policy making in practical wayKeyword: China; CEDAW; Bride Trafficking; International Regime; Compliance to International Regime